2020
DOI: 10.3390/app10134635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diagonal Pattern Training on Trunk Function, Balance, and Gait in Stroke Patients

Abstract: Introduction: Trunk control disability commonly occurs after stroke. This study investigated the effect of diagonal pattern training in the sitting position to improve trunk control ability and gait performance. Method: 46 stroke patients were enrolled in this study. We used single plane training and diagonal pattern training. Additionally, the subjects were randomly assigned to the experiment group (diagonal pattern training) and the control group (single plane training). Diagonal pattern training was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To explain how Tai Ji promotes neuroplasticity, it is essential to understand that, functional movement to perform a particular task, does not depend solely on single plane movement but, rather, a more complex movement involving the activation and inhibition of certain muscle groups ( 36 , 37 ). As such, PNF involves a series of diagonal movement patterns that resembles components of normal functional movements and has been reported to produce greater adaptive plasticity through the increase of neural recruitment of the dorsolateral prefrontal cortex, and the primary motor cortex as compared to the single plane movement ( 6 , 38 ). Although Tai Ji movements are martial art based and do not specifically focus on daily tasks, circular movement in Tai Ji carries similar concepts of PNF diagonal and spiral movement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain how Tai Ji promotes neuroplasticity, it is essential to understand that, functional movement to perform a particular task, does not depend solely on single plane movement but, rather, a more complex movement involving the activation and inhibition of certain muscle groups ( 36 , 37 ). As such, PNF involves a series of diagonal movement patterns that resembles components of normal functional movements and has been reported to produce greater adaptive plasticity through the increase of neural recruitment of the dorsolateral prefrontal cortex, and the primary motor cortex as compared to the single plane movement ( 6 , 38 ). Although Tai Ji movements are martial art based and do not specifically focus on daily tasks, circular movement in Tai Ji carries similar concepts of PNF diagonal and spiral movement.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review on trunk electromyographic (EMG) activity following stroke reported that individuals with stroke demonstrated differences in the trunk EMG recruitment timing, magnitude, and symmetry when comparing the paretic and non-paretic sides ( 5 ). While functional disability such as poor postural control and gait performance in stroke is associated with trunk control disability commonly occurring after a stroke, the trunk component should not be neglected when developing a stroke rehabilitation program ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proprioceptive neuromuscular facilitation (PNF) is a widely used physical therapy approach [ 6 ], which is most commonly used to enhance mobility, motor learning, and motor control in a wide variety of patient populations [ 7 , 8 , 9 , 10 , 11 , 12 ]. This treatment has also been shown to be beneficial in a healthy population to increase expiratory reserve volume (ERV) and vital capacity (VC) [ 13 ], forced vital capacity (FVC), and peak expiratory flow (PEF) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%